AB0747 Interstitial lung disease is independently associated with increased faecal calprotectin levels in systemic sclerosis. (12th June 2018) - Caimmi, C.; Bertoldo, E.; Venturini, A.; Caramaschi, P.; Frulloni, L.; Ciccocioppo, R.; Brunelli, S.; Idolazzi, L.; Gatti, D.; Viapiana, O.; Rossini, M.
Abstract : Background: Interstitial lung disease (ILD) is one of the leading cause of death in systemic sclerosis (SSc). Objectives: The aim of this paper was to evaluate the relationship between faecal calprotectin (FC) and ILD. Methods: 129 outpatients with SSc were enrolled. Data about disease characteristics, in particular lung involvement, were collected and FC was measured. Results: Eighty-seven patients (67.4%) had a limited subset with a mean disease duration of 13.3 (7.1) years. Anti-Scl70 antibodies were found in 35 (27.1%) patients. GI tract involvement was severe/end stage in 3 cases (2.4%). ILD affected 35 patients (27.1%). Median levels of FC were 80 ug/g (157 ug/g). FC was found to be higher in patients with a moderate/severe/end stage score for gastrointestinal tract (p=0.046) and on steroids (p=0.015). In addition, it positively correlated with age (p<0.001). Other than well-known risk factors such as higher mRSS or diffuse subset, patients with ILD had higher values of FC (p<0.001). In multivariate analysis correcting also for factors affecting FC levels (i.e. disease duration, mRSS, Valentini activity score, total Medsger severity score, proton pump inhibitor, anti-Scl-70 antibody, diverticulosis, limited cutaneous subset, faecal calprotectin levels, steroid treatment), diffuse disease subset (p=0.001), higher mRSS (0.04), longer disease duration (0.046), higher severity scores (0.026), higher FC levels (p=0.003) and steroid treatment (0.014) were associated with increased risk of ILD, while diverticulosis was protective. In addition, we ran a second multivariate analysis considering the 110 cases with FC level <275 µg/g, in order to correct for a possible small intestine bacterial overgrowth. Increased FC levels (p=0.019), steroid treatment (p=0.03), higher severity scores (p=0.016) and diffuse disease subset (p=0.002) were confirmed to be associated with ILD. Conclusions: in this paper we have found a possible link between gut inflammation and ILD. Many hypothesis may be done but it is intriguing that these data further support what previously found by other authors (Andreasson et al. 2016), that is a correlation between gut inflammation and dysbiosis and non-gastrointestinal disease manifestation. Our study may support the hypothesis of a role of gut dysbiosis in triggering a pathologic immune response leading to ILD. It may also be that increased FC simply reflects a more severe disease but this still doesn't explain why only ILD was found to be linked with FC. Is it because lung is a filter of molecule (i.e. antigens, cytokines, metabolites, etc.) produced in the gut? Further studies with longitudinal evaluation are warranted. Disclosure of Interest: None declared